Critical success factors for planning in the Bahrain Metro Project - Khalit, Muhammad Ilham; Yusoff, Md Khaizul; Adull Manan, Nor Fazli; Abdul Halim, Nurul Hayati; Tharazi, Izdihar (UiTM Press, 2025)
The success of infrastructure projects is significantly dependent on the planning stage. It is important to determine the successful factor by understanding the process involved with cooperation from all stakeholders. This study aims to determine the critical success factor for planning in the Bahrain Metro Project. A quantitative approach was adopted in the study by participation of 385 professionals including management and execution teams who were involved in the project. The critical success factors identified in the study are; 1) stakeholder engagement, 2) risk management, 3) financial investment, 4) procurement methods, 5) technical specifications, and 6) project ridership. The analysis shows significant relationships between stakeholder engagement, financial investment, procurement methods, and planning success, while risk management and technical specifications had a minimum impact. On the other hand, higher project ridership expectations are not significant to planning in the project. This study highlights the importance of comprehensive planning and informed decision-making in large-scale infrastructure projects, suggesting further research in these areas to enhance project management practices.